Temozolomide chronotherapy in patients with glioblastoma: a retrospective single-institute study. Issue 1 (2nd March 2021) - Damato, Anna R; Luo, Jingqin; Katumba, Ruth G N; Talcott, Grayson R; Rubin, Joshua B; Herzog, Erik D; Campian, Jian L
Abstract: Background: Chronotherapy is an innovative approach to improving survival through timed delivery of anti-cancer treatments according to patient daily rhythms. Temozolomide (TMZ) is a standard-of-care chemotherapeutic agent for glioblastoma (GBM). Whether timing of TMZ administration affects GBM patient outcome has not previously been studied. We sought to evaluate maintenance TMZ chronotherapy on GBM patient survival. Methods: This retrospective study reviewed patients with newly diagnosed GBM from January 1, 2010 to December 31, 2018 at Washington University School of Medicine who had surgery, chemoradiation, and were prescribed TMZ to be taken in the morning or evening. The Kaplan–Meier method and Cox regression model were used for overall survival (OS) analyses. The propensity score method accounted for potential observational study biases. The restricted mean survival time (RMST) method was performed where the proportional hazard assumption was violated. Results: We analyzed 166 eligible GBM patients with a median follow-up of 5.07 years. Patients taking morning TMZ exhibited longer OS compared to evening (median OS, 95% confidence interval [CI] = 1.43, 1.12–1.92 vs 1.13, 0.84–1.58 years) with a significant year 1 RMST difference (−0.09, 95% CI: −0.16 to −0.018). Among MGMT-methylated patients, median OS was 6 months longer for AM patients with significant RMST differences at years 1 (−0.13, 95% CI = −0.24 to −0.019) to 2.5 (−0.43, 95% CI = −0.84 to −0.028). Superiority of morning TMZ at years 1, 2, and 5 (all P < .05) among all patients was supported by RMST difference regression after adjusting for confounders. Conclusions: Our study presents preliminary evidence for the benefit of TMZ chronotherapy to GBM patient survival. This impact is more pronounced in MGMT-methylated patients.